Development and Validation of a Parsimonious Tuberculosis Gene Signature Using the digital NanoString nCounter Platform . (7th January 2022) - Kaipilyawar, Vaishnavi; Zhao, Yue; Wang, Xutao; Joseph, Noyal M; Knudsen, Selby; Prakash Babu, Senbagavalli; Muthaiah, Muthuraj; Hochberg, Natasha S; Sarkar, Sonali; Horsburgh, Charles R; Ellner, Jerrold J; Johnson, W Evan; et al.
Abstract: Background: Blood-based biomarkers for diagnosing active tuberculosis (TB), monitoring treatment response, and predicting risk of progression to TB disease have been reported. However, validation of the biomarkers across multiple independent cohorts is scarce. A robust platform to validate TB biomarkers in different populations with clinical end points is essential to the development of a point-of-care clinical test. NanoString nCounter technology is an amplification-free digital detection platform that directly measures mRNA transcripts with high specificity. Here, we determined whether NanoString could serve as a platform for extensive validation of candidate TB biomarkers. Methods: The NanoString platform was used for performance evaluation of existing TB gene signatures in a cohort in which signatures were previously evaluated on an RNA-seq dataset. A NanoString codeset that probes 107 genes comprising 12 TB signatures and 6 housekeeping genes (NS-TB107) was developed and applied to total RNA derived from whole blood samples of TB patients and individuals with latent TB infection (LTBI) from South India. The TBSignatureProfiler tool was used to score samples for each signature. An ensemble of machine learning algorithms was used to derive a parsimonious biomarker. Results: Gene signatures present in NS-TB107 had statistically significant discriminative power for segregating TB from LTBI. Further analysis of the data yielded a NanoString 6-gene set (NANO6) that when tested on 10 published datasets was highly diagnostic for active TB. Conclusions: The NanoString nCounter system provides a robust platform for validating existing TB biomarkers and deriving a parsimonious gene signature with enhanced diagnostic performance. Abstract : The NanoString nCounter platform is an expedient approach for validating a panel of tuberculosis biomarkers and benchmarking them against each other and for subsequently deriving a parsimonious gene signature with enhanced performance from the data.